Consumer Protection in the Digital Era: Challenges and Solutions from an Islamic Legal Perspective - Dwi Edi Wibowo (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2024)
Technological advancements have transformed buying and selling transactions from conventional to digital, providing convenience for people in conducting transactions. However, this progress also brings new challenges for consumers, particularly regarding protection from fraud, privacy issues, and fulfillment of consumer rights. Consumers' personal data stored in digital systems is vulnerable to misuse, and there is no guarantee that the goods or services received match the agreement with the seller. This study aims to analyze consumer protection challenges in the digital era from an Islamic legal perspective and offers solutions based on sharia principles. This research employs a normative legal method with a literature study approach. The findings reveal that Islamic law, through primary sources such as the Qur'an, Sunnah, Ijma', and Qiyas, as well as muamalah principles such as ash-shiddiq (honesty), al-adl (justice), and al-ihsan (benevolence), provides a strong foundation for consumer protection in the digital era. The study highlights that Islamic law not only emphasizes technical protections but also ethical and moral aspects in digital commerce. In conclusion, consumer protection solutions from an Islamic perspective include three main aspects: transparency in digital transactions, strengthening sharia-based regulations, and enhancing consumer education. By applying the values of justice, honesty, and responsibility in transactions, the goal is to establish safe and fair digital transactions for all parties involved